2023
DOI: 10.1186/s13578-023-01037-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of human PRPS2 filaments

Abstract: Background PRPP synthase (PRPS) transfers the pyrophosphate groups from ATP to ribose-5-phosphate to produce 5-phosphate ribose-1-pyrophosphate (PRPP), a key intermediate in the biosynthesis of several metabolites including nucleotides, dinucleotides and some amino acids. There are three PRPS isoforms encoded in human genome. While human PRPS1 (hPRPS1) and human PRPS2 (hPRPS2) are expressed in most tissues, human PRPS3 (hPRPS3) is exclusively expressed in testis. Although hPRPS1 and hPRPS2 shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…More than 20 different metabolic enzymes form filaments in cells, suggesting that filament assembly is a general mechanism for regulating multiple metabolic pathways (Hvorecny and Kollman, 2023; Lynch et al, 2020; Narayanaswamy et al, 2009; Noree et al, 2010; Park and Horton, 2019; Park and Horton, 2020; Shen et al, 2016; Simonet et al, 2020). For many metabolic enzymes, filament formation is an important mechanism for fine-tuning catalytic activity (Barry et al, 2014; Hansen et al, 2021; Hu et al, 2022; Hunkeler et al, 2018; Hvorecny et al, 2023; Lu et al, 2023; Lynch and Kollman, 2020; Lynch et al, 2017; Polley et al, 2019; Stoddard et al, 2020; Zhong et al, 2022). Here, we demonstrate that filament assembly itself can be directly tuned by phosphorylation, adding an additional layer to an already complex mode of regulation for IMPDH that occurs at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 different metabolic enzymes form filaments in cells, suggesting that filament assembly is a general mechanism for regulating multiple metabolic pathways (Hvorecny and Kollman, 2023; Lynch et al, 2020; Narayanaswamy et al, 2009; Noree et al, 2010; Park and Horton, 2019; Park and Horton, 2020; Shen et al, 2016; Simonet et al, 2020). For many metabolic enzymes, filament formation is an important mechanism for fine-tuning catalytic activity (Barry et al, 2014; Hansen et al, 2021; Hu et al, 2022; Hunkeler et al, 2018; Hvorecny et al, 2023; Lu et al, 2023; Lynch and Kollman, 2020; Lynch et al, 2017; Polley et al, 2019; Stoddard et al, 2020; Zhong et al, 2022). Here, we demonstrate that filament assembly itself can be directly tuned by phosphorylation, adding an additional layer to an already complex mode of regulation for IMPDH that occurs at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoribosyl pyrophosphate synthetase (PRPS) is a key rate-limiting enzyme in nucleotide synthesis, containing three subtypes: PRPS1, PRPS2, and PRPS3. 7 It has been Zhenzhen Chen and Lei Wei contributed equally to the study.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoribosyl pyrophosphate synthetase (PRPS) is a key rate‐limiting enzyme in nucleotide synthesis, containing three subtypes: PRPS1, PRPS2, and PRPS3. 7 It has been found that PRPS1 and PRPS2 play important regulatory roles in different malignant tumors. PRPS1 is overexpressed in melanoma and accelerates tumor progression by promoting cell growth, metastasis, and suppressing cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%